Design of a High-Speed OFDM-SAC-OCDMA-Based FSO System Using EDW Codes for Supporting 5G Data Services and Smart City Applications - Singh, Mehtab; Kříž, Jan; Kamruzzaman, M. M.; Dhasarathan, Vigneswaran; Sharma, Abhishek; Abd El-Mottaleb, Somia A. (Frontiers in Physics, 2022)
A novel free space optics (FSO) system is introduced in this article by combining orthogonal frequency division multiplexing (OFDM) with spectral amplitude coding optical code division multiple access (SAC-OCDMA) to be implemented in 5G technology and smart cities. Enhanced double-weight (EDW) codes are used as signature codes, while for the detection technique, single photodiode detection (SPD) is applied for the SAC-OCDMA system. OFDM with a four-quadrature amplitude modulation (4-QAM) scheme is assigned to the three users in the SAC-OCDMA system, each carrying 15 Gbps. Adverse weather conditions, such as clear, fog, haze, rain, and dust storm, that affect the FSO channel are considered. The performance of the proposed system is evaluated in terms of log of bit error rate and received power at different propagation distances. The simulation results show successful transmission of 3 × 15 Gbps with a propagation range of 3.45 km under clear air and 1.316, 1.045, and 0.7 km under rain conditions (light, medium, and heavy rain) with a received power of −12.6 dBm. As for haze conditions, the range and received power are 2.391 km with −13 dBm for low haze, 1.591 km with −12.7 dBm for medium haze, and 1.025 km with −12.6 dBm for heavy haze. The range is reduced and becomes 1.085, 0.784, and 0.645 km under fog conditions (light, medium, and heavy fog) with −12.6 dBm received power. Furthermore, the system achieved a range of 0.681, 0.232, and 0.102 km under dust conditions (light, medium, and heavy dust) with a received power of −16 dBm.